Soluble TNF mediates amyloid-independent, diet-induced alterations to immune and neuronal functions in an Alzheimer’s disease mouse model - MacPherson, Kathryn P.; Eidson, Lori N.; Houser, Madelyn C.; Weiss, Blaine E.; Gollihue, Jenna L.; Herrick, Mary K.; de Sousa Rodrigues, Maria Elizabeth; Sniffen, Lindsey; Weekman, Erica M.; Hamilton, Adam M.; Kelly, Sean D.; Oliver, Danielle L.; et al. (Frontiers in Cellular Neuroscience, 2023)
Introduction: Increasing evidence indicates that neurodegenerative diseases, including Alzheimer’s disease (AD), are a product of gene-by-environment interplay. The immune system is a major contributor mediating these interactions. Signaling between peripheral immune cells and those within the microvasculature and meninges of the central nervous system (CNS), at the blood-brain barrier, and in the gut likely plays an important role in AD. The cytokine tumor necrosis factor (TNF) is elevated in AD patients, regulates brain and gut barrier permeability, and is produced by central and peripheral immune cells. Our group previously reported that soluble TNF (sTNF) modulates cytokine and chemokine cascades that regulate peripheral immune cell traffic to the brain in young 5xFAD female mice, and in separate studies that a diet high in fat and sugar (HFHS) dysregulates signaling pathways that trigger sTNF-dependent immune and metabolic responses that can result in metabolic syndrome, which is a risk factor for AD. We hypothesized that sTNF is a key mediator of peripheral immune cell contributions to gene-by-environment interactions to AD-like pathology, metabolic dysfunction, and diet-induced gut dysbiosis. Methods: Female 5xFAD mice were subjected to HFHS diet for 2 months and then given XPro1595 to inhibit sTNF for the last month or saline vehicle. We quantified immune cell profiles by multi-color flow cytometry on cells isolated from brain and blood; metabolic, immune, and inflammatory mRNA and protein marker biochemical and immunhistological analyses, gut microbiome, and electrophysiology in brain slices were also performed. Results: Here, we show that selective inhibition of sTNF signaling via the biologic XPro1595 modulates the effects of an HFHS diet in 5xFAD mice on peripheral and central immune profiles including CNS-associated CD8+ T cells, the composition of gut microbiota, and long-term potentiation deficits. Discussion: Obesogenic diet induces immune and neuronal dysfunction in 5xFAD mice and sTNF inhibition mitigates its effects. A clinical trial in subjects at risk for AD due to genetic predisposition and underlying inflammation associated with peripheral inflammatory co-morbidities will be needed to investigate the extent to which these findings translate to the clinic.